Manajemen Konflik Efektif: Strategi Mengubah Ketegangan Menjadi Peluang Belajar dan Keberhasilan Pembelajaran - Alifana, Fairus Tahta; Rofiah, Lia Afifatur; Zain, Tajudddin; Mu’alimin, Mu’alimin (Jurnal Manajemen Pendidikan Islam, 2024)
This study explores effective conflict management strategies to transform tension into learning opportunities and educational success. The research employs a qualitative approach with a literature review method to analyze various strategies such as negotiation, mediation, and collaboration. The findings indicate that well-managed conflicts can enhance learning quality, build interpersonal skills, and foster innovation within educational settings. This study provides new insights into the importance of leveraging conflicts as catalysts for learning and organizational development in education.